Determinants of Islamic Social Reporting Disclosure: a Meta-Analysis - Pratiwi, Maisya; Mohammed Inuwa, Abubakar (IKONOMIKA, 2025)
Islamic Social Reporting (ISR) serves as a corporate governance mechanism to ensure accountability and sustainability. Over the past decade, increasing attention has been devoted to studying the determinants influencing ISR disclosure, such as profitability, company size, and the Sharia Supervisory Board (SSB). However, findings across these studies have been diverse and occasionally contradictory due to the heterogeneity in sample characteristics. This study aims to conduct a meta-analysis of prior empirical research to provide a comprehensive and holistic understanding of the effects of profitability, company size, and SSB presence on ISR disclosure. The findings indicate that company size has a significant positive effect on ISR disclosure, suggesting that larger firms are more likely to engage in comprehensive social reporting due to increased scrutiny and a need for legitimacy. Conversely, the effects of profitability and Sharia Supervisory Board on ISR were found to be positive but not statistically significant, implying that these factors alone do not robustly predict ISR practices. These findings contribute to the theoretical understanding of ISR and offer practical implications for policymakers and practitioners aiming to enhance transparency and accountability in firms. Policymakers can formulate regulations to encourage ISR disclosure, while practitioners can develop ISR strategies aligned with ethical and sustainability goals to meet stakeholder expectations for transparency and accountability. The study concludes with recommendations for future research to address the observed gaps and expand the empirical base of ISR literature.